EFFICIENCY OF CZECH INTERNATIONAL DEVELOPMENT PROJECTS WITH THE FOCUS ON PROJECT MANAGEMENT - Dufková, Gabriela; Šaroch, Stanislav, 1970-; Vlčková, Jana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
International development (ID) assistance is nowadays predominantly delivered in the form of international development projects. Despite their importance, these projects often tend to underperform both in terms of internal and external project results. Literature therefore explores underlying reasons behind these project failures and identifies poor project management as one of the common pitfalls. However, the Czech Republic is not, as a relatively new and small donor, considered in the scope of these studies. This dissertation thesis therefore aims to cover this gap and aims to provide a holistic view of Czech international development projects implemented abroad. It has three main areas of interests, namely project performance, project management (PM) and the influence of project management on project results. Based on an analysis of bilateral ID projects fully or partially funded by the Czech Development Agency between 2016 and 2019 abroad, the thesis suggests that their results are generally better than those funded by donors explored by the existing literature. This might be caused by different project characteristics and delivery schemes. The thesis furthermore proposes that the financial project delivery is influenced by the sector of implementing organisation, type of financing, project size and sector, and the aid-receiving country, while its timely delivery depends only on the project size and sector. Finally, the section proposes that Czech aid flows are currently unable to boost Czech export flows to the aid-receiving countries. In terms of project management, a new survey data was used to identify project management methodologies and tools applied by project leaders on Czech ID projects. Having in mind the current trends in the industry, the thesis furthermore explores the influence of the organisation’s sector on project delivery and reveals differences between non-profit, for-profit and public organisations.
For-profit organisations tend to be more focused on scoping and scheduling, while non-profit organisations find stakeholder management more important than other sectors. The thesis moreover indicates that there is no difference between the implementing organisations when considering the internal results and that all sectors seem to place greater importance on achieving these results rather than the external ones. Finally, for-profit companies seem less interested in achieving long-term project impact and long-term economic sustainability after the project end compared to other players. Last but not least, the thesis explores the link between the application of PM tools and the achieved project results. It indicates that the internal project results are positively influenced by the use of milestone planning and logical framework while the external project results are positively affected only by the internal project outcome. Based on the findings mentioned above, the thesis proposes several recommendations for the PM practitioners, implementing organisations, Czech Development Agency and policy makers.
Vedoucí práce: Stanislav Šaroch
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní ekonomické vztahy [obor disert. práce]; disertace; dissertations